2015
DOI: 10.11646/zootaxa.3957.3.7
|View full text |Cite
|
Sign up to set email alerts
|

First record of the orchid bee genus Eufriesea Cockerell (Hymenoptera: Apidae: Euglossini) in the United States

Abstract: The orchid bee genus Eufriesea Cockerell is documented for the first time from the southwestern United States, extending its apparent range north well beyond its previous tropical/subtropical boundaries. Eufriesea coerulescens (Lepeletier de Saint Fargeau 1841) is recorded from the Guadalupe Mountains of western Texas and southeastern New Mexico, USA. Whether E. coerulescens is resident in the USA, or merely a vagrant from Mexico, remains unclear. Distinctive morphological traits shared with the holotype are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…In contrast, they found low to complete absence of suitable habitat in southernmost Texas and southern Arizona for E. polychroma, thus supporting the idea of a long-distance dispersal event, as Minckley and Reyes (1996) inferred based on the heavily worn wings of the captured specimen. Unlike the specimen of E. polychroma, the two males of Eufriesea collected in the USA displayed no signs of major wing damage, and thus Griswold et al (2015) suggested that these specimens might be members of a persistent bee population, rather than long-distance transient vagrants. If this were correct, a SDM would predict highly suitable habitat for this species of Eufriesea in the southern USA, as in the case of E. dilemma.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…In contrast, they found low to complete absence of suitable habitat in southernmost Texas and southern Arizona for E. polychroma, thus supporting the idea of a long-distance dispersal event, as Minckley and Reyes (1996) inferred based on the heavily worn wings of the captured specimen. Unlike the specimen of E. polychroma, the two males of Eufriesea collected in the USA displayed no signs of major wing damage, and thus Griswold et al (2015) suggested that these specimens might be members of a persistent bee population, rather than long-distance transient vagrants. If this were correct, a SDM would predict highly suitable habitat for this species of Eufriesea in the southern USA, as in the case of E. dilemma.…”
Section: Introductionmentioning
confidence: 89%
“…In the Andes, except for the monotypic genus Aglae Lepeletier de Saint Fargeau & Serville, specimens of one or two species of the remaining four genera of Euglossini have been collected at elevations above 2500 m (Gonzalez and Engel 2004, Perger 2015. In the USA, in addition to Eufriesea, two other orchid bee species have been documented: Euglossa dilemma Bembé & Eltz [as E. viridissima (Friese)] in southern Florida and Eulaema polychroma (Mocsáry) in southern Arizona and southernmost Texas (Minckley and Reyes 1996, Búrquez 1997, Skov and Wiley 2005, Griswold et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations